Electroactive Polymer Gel Robots Modelling and Control of Artifical Muscles - Otake, Mihoko; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
The monograph written by Mihoko Otake combines ideas from chemistry and physics, material science and engineering for the revolutionary development of the so-called gel robots. Electroactive polymers are introduced to build new types of muscular-like actuation for deformable robots. The coverage spans from modelling and design to the development, control and experimental testing. A number of methods are proposed for describing the shapes and motions of such systems. The results are demonstrated for beam-shaped gels curling around an object and starfish-shaped gel robots turning over.
I: Modelling -- Adsorption-Induced Deformation Model of Electroactive Polymer Gel -- Parameter Identification by One Point Observation -- II: Design -- Interaction-Based Design of Deformable Machines -- Spatially-Varying Electric Field Design by Planer Electrodes -- Shape Design through Geometric Variation -- III: Control -- Polarity Reversal Method for Shape Control -- Lumped-Driven Method for Motion Control -- Conclusion and Future Works.
Keywords: Engineering; Polymers; Artificial intelligence; Systems theory; Control engineering systems; Biomedical engineering; Engineering; Control , Robotics, Mechatronics; Polymer Sciences; Artificial Intelligence (incl. Robotics).; Systems Theory, Control; Biomedical Engineering